Enforcement and Effectiveness of Consumer Law (Ius Comparatum - Global Studies in Comparative Law, 2018)
The book focusses on the enforcement of consumer law in order to identify commonalities and best practices across nations. It is composed of twenty-eight contributions from national rapporteurs to the IACL Congress in Montevideo in 2016 and the introductory comparative general report. The national contributors are drawn from across the globe, with representation from Africa (1), Asia (5), Europe (15), Oceania (2) and the Americas (5). The general report proposes a general introduction to the question of enforcement and effectiveness of consumer law. It then proceeds to identify the variety of ways in which national legislatures approach this question and the diversity of mechanisms put in place to address it. The general report uses examples drawn from the reports to illustrate common approaches and to identify more original or distinct unique approaches, taking into account the reported strengths and weaknesses of each. The general report consistently points readers to particular national reports on specific issues, inviting readers to consult these individual contributions for more details. The national contributions deal with the following areas: the national legal framework for consumer protection, the general design of the enforcement mechanism, the number and characteristics of consumer complaints and disputes, the use of courts and specialized agencies for the enforcement of consumer law, the role of consumer organizations and of private regulation in the enforcement of consumer law, the place of collective redress mechanism and of alternative dispute resolution modes, the sanctions for breaches of consumer law and the nature of external relations or cooperation with other countries or international organizations. These enriching national and international perspectives offer a comprehensive overview of the current state of consumer law around the globe.